Effective field theory and inelastic dark matter results from XENON1T - Aprile, Elena; Guida, Matteo; Hammann, Robert; Hötzsch, Luisa; Lindner, Manfred; Marrodán Undagoitia, Teresa; Terliuk, Andrii; Wolf, Thomas (Physical review, 2024)
In this work, we expand on the XENON1T nuclear recoil searches to study the individual signals of dark matter interactions from operators up to dimension eight in a chiral effective field theory (ChEFT) and a model of inelastic dark matter (iDM). We analyze data from two science runs of the XENON1T detector totaling 1 t×yr exposure. For these analyses, we extended the region of interest from [4.9,40.9] keVNR to [4.9,54.4] keVNR to enhance our sensitivity for signals that peak at nonzero energies. We show that the data are consistent with the background-only hypothesis, with a small background overfluctuation observed peaking between 20 and 50 keVNR, resulting in a maximum local discovery significance of 1.7⁢𝜎 for the Vector⊗Vectorstrange ChEFT channel for a dark matter particle of 70 GeV/𝑐2 and 1.8⁢𝜎 for an iDM particle of 50 GeV/𝑐2 with a mass splitting of 100 keV/𝑐2. For each model, we report 90% confidence level upper limits. We also report upper limits on three benchmark models of dark matter interaction using ChEFT where we investigate the effect of isospin-breaking interactions. We observe rate-driven cancellations in regions of the isospin-breaking couplings, leading to up to 6 orders of magnitude weaker upper limits with respect to the isospin-conserving case.
XENON Collaboration: E. Aprile, M. Guida, R. Hammann, L. Hötzsch, M. Lindner, T. Marrodán Undagoitia, A. Terliuk, T. Wolf [und 152 weitere]
Gesehen am 04.06.2025